It is the Spirit who gives life : new directions in pneumatology - Bordeianu, Radu (The Catholic University of America Press, 2022)
"This volume gathers essays authored by eleven world-renowned theologians. Each contribution originated as a public lecture addressed to theologians and an educated general audience, followed by a private colloquium in which the lecturers conferred with scholars who are experts in the field. Thus, the present volume offers a multifaceted approach to Pneumatology, in an ecumenical spirit"--